INTEGRATED GEOTOURISM ASSESSMENT FRAMEWORK: APPLICATION OF THE ABC-GAM MODEL IN IDENTIFYING PILOT GEOPARKS (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
The article examines the theoretical and methodological foundations of geotourism development and the formation of pilot geoparks based on modern integrated approaches. The main objective of the study is to develop a well-defined framework for assessing the geotourism potential of territories through the synthesis of the ABC (Abiotic, Biotic, Cultural) concept and the GAM (Geosite Assessment Model) quantitative model. The proposed methodology reduces expert subjectivity through a structured semi-quantitative assessment procedure by separating the Main Values of geosites from the Additional Values. Projecting the calculated data onto a two-axis 9-zone GAM matrix enables strategic screening of the area, identification of the geopark's sustainable "core", and definition of investment priorities. The paper substantiates the strategic importance of localizing this model for the Republic of Armenia as an effective tool for geoconservation and the socio-economic sustainable development of remote and border communities.
Keywords: geotourism; geosite; ABC concept; GAM model; assessment matrix; pilot geopark; geoconservation; sustainable development